HERMENEUTIKA SEBAGAI TEORI INTERPRETASI DALAM TRADISI BARAT - Hilyati Aulia (LP2M Universitas PTIQ Jakarta, 2023)
Hermeneutics functions as a theory of interpretation, closely related to language. One that cannot be separated from language is text, which requires a series of reading tools to understand it, one of which is the theory of hermeneutics. This article aims to find out the thoughts of Schleiermacher and Dilthey as the originators of romantic hermeneutics and their application in hadith. This article is qualitative in nature with literature data related to Schleiermacher and Dilthey's hermeneutical thinking and hadith about women's leadership. Through a philosophy of science approach, this article finds that Schleiermacher is the father of modern hermeneutics whose ideas about the mental world were developed by Dilthey who explained about the socio-historical world. Through these readings, women can become leaders